Flexible lithium-sulfur battery
A sulfur-containing polymer-filled separator and lithium metal anode with a graphene/sulfur cathode interlayer enhance lithium-sulfur battery performance, addressing flexibility and polysulfide issues, achieving high energy density and stability.
Patent Information
- Application Number
- JP2024160770
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-20
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-14
AI Technical Summary
Current flexible lithium-ion batteries have low energy density, and existing lithium-sulfur batteries face challenges in maintaining mechanical flexibility and preventing polysulfide shuttle effects, while commercially available separators fail to effectively block polysulfides without increasing weight and thickness.
A separator for lithium-sulfur batteries is developed using a porous membrane filled with sulfur-containing polymers, reducing pore sizes to prevent polysulfide passage while maintaining flexibility and conductivity, combined with a lithium metal anode and a graphene/sulfur cathode protected by a boron nitride/graphene interlayer.
The solution achieves high energy density and mechanical flexibility, with the battery maintaining excellent electrochemical performance and safety through 800 cycles, even in folded states, with improved polysulfide blocking and reduced weight.
Smart Images

Figure 2025004017000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a high performance flexible lithium-sulfur battery and its components, particularly in a flexible battery. Particularly suitable for use are anodes and separators. [Background technology]
[0002] There is an urgent need for flexible, high-performance batteries to power flexible / wearable electronic devices. Although flexible lithium-ion batteries are required, current flexible batteries have relatively low energy density. Although the energy density of lithium-sulfur batteries is much higher, the flexibility of lithium-sulfur batteries is Pond development remains a major challenge.
[0003] Lithium-sulfur (Li-S) batteries have high theoretical energy density and low cost. The environmentally friendly sulfur active material is abundant in nature, making it ideal for use in current lithium-ion batteries (LiBs). Flexible Li-S batteries are considered a promising alternative that can provide better performance than conventional batteries. Stable electrochemical performance when repeatedly bent, folded, and stretched It is necessary to provide a cathode, an anode, a separator, an electrolyte, and a current collector. All elements within a flexible battery are mechanically flexible enough to withstand repeated mechanical deformation. In addition, to prevent battery failure, continuous electron / ion paths must be maintained. Sulfur, carbon nanotubes, graphene, carbonized polymers, commercial carbon Flexible sulfur containing fibers and their composites in combination with a flexible conductive host Yellow cathodes are known. They are also used to reduce the shuttle effect of polysulfides (PSUs). In recent years, functional (modified) interlayers have been developed for the cathode. In particular, modified boron nitride nanosilicates The selective interlayer of FBN / graphene (FBN / G) reduces the charge transfer resistance and improves the shuttle However, only the improved flexible cathodes have shown great potential to alleviate the problems. cannot guarantee good performance of the flexible Li-S full battery.
[0004] There are almost no reports on flexible lithium-based anodes. The main challenge with the node is its low mechanical flexibility, which makes it difficult to rotate after bending and twisting. Permanent distortions, including wrinkles, creases, or buckling, are difficult to repair. In addition, the infinite volume change of the Li anode and the dendrimers Branch growth also has a significant negative impact on the cycle life of lithium metal anodes. Two strategies for fabricating flexible lithium anodes have been reported, in which conductive poly( Ethylene terephthalate (PET) and boron nitride / Ti3C2 Mxene The lithium foil is mechanically rolled together with a flexible material such as lithium carbide to form a thin film. Although the mechanical flexibility of the wire has been improved, the flexible material used is Li-plated / striped. The problem of the volume change of the anode during the charging cycle is Another approach to development is desired. Summary of the Invention [Problem to be solved by the invention]
[0005] Commercially available separators for Li-S batteries are used to separate the Li + impede the passage of These commercially available The large pores in the separator allow Li +Not only does it pass through the soluble polysulfides, but it also passes through the soluble polysulfides over time. The general strategy to improve the separator is mainly to improve the filter. The step of coating the separator with an additional layer that acts as a separator. The thickness and weight of the layers lead to an increase in the total thickness and weight of the entire battery, resulting in a loss of gravimetric energy. This leads to a decrease in density and volumetric energy density. Also, the flexibility of such separators is not advantageous. Not used.
[0006] Due to the increasing use of the Internet of Things (IoT) and flexible / wearable electronic devices, Therefore, there is an urgent need for flexible power sources with high energy density, electrochemical sustainability, and light weight. Among various novel battery systems, the lithium-sulfur (Li-S) battery has the theoretical potential Energy-dense, low-cost, environmentally friendly sulfur active material is naturally abundant Therefore, it is a promising alternative that can outperform current lithium-ion batteries (LIBs). It is believed that flexible and high performance power supply for flexible wearable electronic devices is required. There is an urgent need for new batteries.
[0007] To obtain a flexible Li-S full battery with excellent electrochemical and mechanical performance, three The flexibility of all components (cathode, anode and separator) must be guaranteed. do not have. [Means for solving the problem]
[0008] In a first aspect, the present invention provides a separator for an energy storage device, comprising: The device includes one or more porous membranes of a material selectively permeable to Li-ions, and at least one of the pores of the porous membrane is Some of the pores in the sulfur-containing polymers are associated with Li At least one order of magnitude smaller than the pores of the ion-selectively permeable material.
[0009] The pores in the porous membrane have a diameter greater than 100 nm and a maximum diameter of about 10 micrometers (μm ) in different shapes and sizes. In one embodiment, the porous sulfur polymer After filling with pores, the original pore size of the membrane is substantially reduced to below 50 nm. The average pore size is preferably 0.5 digits (a factor of 2 or more), more preferably 0.75 digits (a factor of 5 or more). and most preferably by an order of magnitude or more (a factor of 10 or more).
[0010] In a particularly preferred embodiment, the pores of the sulfur-containing polymer are It is approximately one order of magnitude (a factor of 10 or more) smaller than the pores in the porous membrane.
[0011] In a related aspect, the invention provides a separator for an energy storage device, the separator comprising: The reactor includes one or more microporous membranes of a material selectively permeable to Li-ions, and the microporous membranes At least a portion of the metric pores are associated with the nanoporous sulfur-containing polymer.
[0012] Desirably, the sulfur-containing polymer is heated to a temperature of 250° C. or higher, more preferably 275° C. or higher, and most preferably 100° C. or higher. Preferably, the melting point is 280° C. or higher. The preferred sulfur-containing polymer is -It is.
[0013] Commercially available separators typically contain membranes with average pore sizes greater than 100 nm. In the present invention, the average pore size after modification with sulfur-containing polymer is about 10 nm.
[0014] Suitably, the separator membrane comprises a microporous polymer. Suitably, the membrane has a surface area of It has a microporosity of about 20% to about 70%.
[0015] Desirably, the sulfur-containing polymer is selectively permeable to lithium ions and the electrolyte. It is preferably nanoporous but not permeable to polysulfides. The sulfur-containing polymer has a pore size ranging from about 5 nm to about 20 nm. The preferred porosity of the polymer is in the range of 10% to 30% of the surface area of the membrane.
[0016] In a preferred embodiment, the membrane thickness is about 10 μm to 50 μm, more preferably about 20 μm to 35 μm, and most preferably in the range of about 25 μm to 28 μm.
[0017] In the separator defined herein, the sulfur-containing polymer is at least one of the pores of the membrane. Filling at least a portion of the pores of the separator membrane reduces the microporosity of the membrane and reduces the Polysulfide that passes through the separator while allowing lithium ions to pass through the separator. More preferably, substantially all of the pores of the membrane are filled with sulfur-containing ions after modification. The sulfur-containing polymer is either not present on the surface of the membrane or is filled with the separator. To avoid making the data unnecessarily heavy and / or thick, there is very little It is preferred that the sulfur-containing polymers are present only in small amounts in the membrane, rather than on the membrane surface. Restricting at least a portion of the pores is an energy storage device including the separator of the present invention. The polysulfides are eliminated without substantially increasing the total thickness and weight or energy of the This advantageously results in a better separator for removing the is more effective at preventing polysulfide passage / shuttle than conventional separators However, in the prior art, a polysulfide filtration layer or coating is added to the separator. There is no reduction in gravimetric and volumetric energy density observed with the separator.
[0018] Preferably, the separator of the present invention has a dielectric constant of 6.87 mScm at 25° C. -1 Ion conduction exceeding One exemplary separator has a conductivity of about 6.41 mScm at 25° C. -1 Ion It has conductivity.
[0019] Suitably, during manufacture, the pores of the separator membrane are filled with a sulfur-containing polymer. The sulfur-containing polymer provided in the micropores of the membrane is preferably rendered nanoporous via a phase inversion process. It has been shown that nanopores can be easily generated in sulfur-containing polymers using a phase inversion process. Thus, the inclusion of sulfur-containing polymers improved the overall thermal and mechanical properties. This also improves the stability of the actuator.
[0020] Preferably, the total amount of sulfur-containing polymer in the membrane is about 20 wt.% or less, more preferably It is 10% by weight or less.
[0021] Suitably, the mass loading of the sulfur-containing polymer is about 0.20 mg / cm -2 ~ approx. 0.4 mg / cm -2 , more preferably about 0.10 mg / cm -2 ~about 0.2mg / cm -2 is .
[0022] Most preferably, substantially all of the pores of the membrane are filled with the porous sulfur-containing polymer. However, the inclusion of the filler polymer increases the total weight of the separator by more than about 10% by weight. Preferably, the sulfur-containing polymer is about 20% by weight or less, more preferably about 15% by weight or less. % by weight or less, and most preferably about 10% by weight or less.
[0023] In a preferred embodiment, the material of the membrane is different from the sulfur-containing polymer that fills the pores of the membrane.
[0024] In a particularly preferred embodiment, the sulfur-containing polymer is a modified or unmodified aromatic polysulfone. sulfone, preferably polyarylethersulfone (PAES), e.g. polysulfone In some embodiments, quaternary ammonia polysulfone polymers are less preferred. Not like that.
[0025] In some embodiments, the membrane is a laminate of two or more membranes of a Li-ion selectively permeable material. It is in the form of
[0026] Desirably, the sulfur-containing polymer is heated to a temperature of 250° C. or higher, more preferably 275° C. or higher, and most preferably 100° C. or higher. Preferably, the material has a melting point of 280° C. or higher. At the melting point, the porosity of the membrane is lost. The thermal fuse of the energy storage device is used to shut down the device. It can be advantageously used as
[0027] Desirably, the material of the membrane is an organic polymer, which may be modified or unmodified; In particular, it includes polyolefin polymers. Particularly preferred are organic polymers which are unmodified polyolefins. More preferably, the membrane is made of polyethylene, polypropylene, or a combination thereof. Includes matching.
[0028] In a particularly preferred embodiment, the separator of the present invention is a flexible separator. The flexibility of the actuator is determined by its thickness and stiffness. Particularly preferred are separators that can be folded and / or manually retracted. stomach.
[0029] In a particularly preferred embodiment, the thickness of the film is substantially the same after treatment with the sulfur-containing polymer. For example, it is about 26 microns.
[0030] Desirably, the wettability of the modified film is substantially the same as the wettability of the untreated film. .
[0031] In a second aspect of the present invention, there is provided a method for producing a separator for an energy storage device, the method comprising the steps of: A method for facilitating data transfer is provided. (i) an energy storage device comprising one or more porous membranes of at least one Li-ion selectively permeable material; - providing a porous separator for a storage device; (ii) at least one sulfur atom in the pores of the membrane of the at least one Li-ion selectively permeable material; forming a sulfur-containing polymer modified membrane by filling the sulfur-containing polymer; (iii) introducing pores into the sulfur-containing polymer, the pores of the sulfur-containing polymer being , a step that is at least one order of magnitude smaller than the pores of the Li-ion selectively permeable material; and Includes.
[0032] In a related aspect of the present invention, a method for producing an energy storage device is provided, comprising the steps of: A method for preparing a separator is provided. (i) an energy storage device comprising one or more microporous membranes of at least one Li-ion selectively permeable material; - providing a porous separator for a storage device; (ii) at least one sulfur atom is introduced into the micropores of the membrane of the at least one Li-ion selectively permeable material; forming a sulfur-containing polymer modified membrane by filling a sulfur-containing polymer; (iii) introducing nanopores into the sulfur-containing polymer; Includes.
[0033] Desirably, the step of forming the sulfur-containing polymer modified membrane is carried out, for example, by solvent casting. Thus, a solution of the sulfur-containing polymer in a solvent is mixed with at least one Li-ion selectively permeable material. The method includes providing a surface membrane comprising the steps of:
[0034] Suitably, the method includes increasing the thickness of the sulfur-containing polymer layer to a desired level, preferably about 200 In one embodiment, the applying and adjusting steps further include adjusting the The method includes blading a sulfur-containing polymer-modified membrane followed by removal of the solvent. Suitably the solvent is removed by vacuum assisted evaporation. This can be done.
[0035] The method may, for example, involve wiping or brushing excess polymer off the surface of the membrane. and removing excess sulfur-containing polymer from the membrane by (brushing) This step may include removing excess sulfur-containing polyimide that is not in the pores from the separator. In other words, the excess sulfur-containing polymer is removed from the polymer. In one embodiment, the excess sulfur-containing polymer is removed from the surface but not from the pores. The ions are removed from the membrane surface by vacuum.
[0036] Preferably, the thickness of the separator is the same as the thickness before the sulfur-containing polymer is introduced into the pores of the membrane. Qualitatively the same.
[0037] Preferably, the nanopores are formed in the modified membrane by treating the modified membrane with a phase inversion wetting process. The modification is introduced into the sulfur-containing polymer during the phase inversion wetting process in an organic solvent such as DMF. and then contacted with a non-solvent phase, such as water, for example by immersion. This results in the formation of two phases: a polymer-rich phase and a polymer-poor phase. The solvent exchange process induces nanoporous structures at the phase interface and within the pores of the membrane. is formed.
[0038] The lithium metal anode for the energy storage device containing the conductive fabric is made of one or more parent lithium It has also been described as having an interconnected network of fibers modified with an acrylic material.
[0039] Suitably the fabric is a flexible fabric.
[0040] Desirably, the lithium metal is deposited in the gaps or spaces between the functionalized (modified) fibers. It is insertable, retractable, and removable from.
[0041] In a related aspect, the present invention provides a lithium-gold conductive material for an energy storage device that includes a conductive fabric. a metal anode comprising an interconnected network of fibers modified with one or more lithophilic materials; The lithium metal is also formed from a lithophilic material. It will be understood that the nanostructure is located within the nanoparticles.
[0042] In a related aspect, an energy storage device is provided that includes a flexible conductive fabric having an interconnected network of fibers. A lithium metal anode for a gas storage device is provided, wherein each fiber has one or more lithiophilic The fibers are modified with a material whereby lithium metal is intercalated in the interstices or spaces between the modified fibers. It is storable and removable.
[0043] The flexible anode of the present invention is free from localized extraction of one or more of wrinkles, folds, and buckles. The flexible anode of the present invention is more resistant to permanent distortion caused by lithium metal. , compared to lithium metal, the volume generated during the lithium stripping / plating cycle More resistant to change.
[0044] The excellent mechanical properties and hierarchical nanostructured network of the modified fabric anodes are the This contributes greatly to the unprecedented flexibility and stability of these flexible lithium anodes.
[0045] In the lithium metal anode defined herein, the lithium metal anode is preferably or interconnected, preferably interlaced (intertwined or interwoven fibers) Includes fabrics having a network of interconnected, interlaced, or interwoven fibers. The interwoven fiber network forms a microstructure with a 3D fibrous structure, and the interfiber voids and / or spaces are formed in the entire surface where lithium metal can be injected, stored, and removed. In other words, the microstructure of the fiber network is The nanostructure provided by the lithophilic material on the fiber allows the fabric to function as a lithium metal host. It enables the device to function as a
[0046] Repeatedly bent and folded for over 3000 cycles without breakage or significant loss of performance Because of the need to be folded, highly flexible fabrics are preferred for flexible Li-S energy storage devices. Also, only fabrics with sufficiently high electrical conductivity and large surface area can be used to produce flexible Li- S energy storage devices. Furthermore, an ideal fabric would be suitable for use in energy storage devices. Further preferred fabrics are chemically stable under the environmental conditions experienced in storage devices. on the fabric to improve the surface chemistry of the fabric, particularly with respect to wettability of molten lithium (i.e. It retains these properties after hydrothermal treatment, allowing the growth of metal oxides such as MnO2. Finally, the fabric must be able to maintain its mechanical strength and elasticity under a significant amount of bending, folding, and stretching. Therefore, carbon fabrics need to maintain the required high mechanical flexibility and elasticity. In addition, the preferred fabric is one of the suitable materials that has excellent thermal conductivity and other properties. 3D porous structure / 3D microstructure suitable for restricting the formation of Li dendrites, which are the building blocks of Li-ionization Suitably the fabric is a carbon fabric. Preferably the fabric is a conductive carbon fabric. Which conductive fabric is used? The preferred fabric has an electrical resistivity of 1.4×10 -3 Ω cm.
[0047] Suitably, the fabric is modified with nanostructures of one or more lithophilic materials. Modification of the fabric fibers with lithophilic materials aids the adsorption of lithium metal by the fabric host. More suitably, the nanostructure is a 3D lithophilic nanostructure, preferably a fabric. A particularly preferred embodiment is in the form of nanoflakes or nanosheets, which significantly increases the surface area. In an embodiment, the 3D lithophilic nanostructure comprises MnO2. Most preferably, the 3D lithophilic nanostructure comprises MnO2. The titanium nanostructure comprises 3D hierarchical MnO2 nanosheets. Suitably, the nanostructure is a fabric fiber. It is manufactured uniformly over a long period of time.
[0048] Desirably, the lithium metal is associated with the textile fibers and / or nanostructures. Preferably, lithium metal is associated with the textile fibers and nanostructures.
[0049] Suitably, during the manufacture of the anode, lithium metal is added to the anode in the form of a molten lithium metal pour. Preferably, the lithium loading on the lithium metal anode is about 2 m gcm -2 ~about 10mg cm -2 In some embodiments, the lithium metal loading is preferably 3 mg / cm -2 or 6 mg cm -2 It is.
[0050] In a particularly preferred embodiment, the lithium metal anode of the present invention is a flexible lithium metal anode. A node.
[0051] (i) modifying a conductive fabric with one or more lithophilic materials; (ii) associating the modified fabric with lithium metal; A method for preparing a lithium metal anode for an electrochemical cell is also described, including:
[0052] Suitably the fabric is flexible.
[0053] Preferably, the fabric is a conductive fabric, such as a conductive carbon fabric, and most preferably a carbon fabric, e.g. For example, commercially available carbon cloth.
[0054] Desirably, the step of modifying the fabric with a lithophilic material comprises, for example, potassium permanganate. This involves the hydrothermal method using aluminum powder, concentrated hydrochloric acid, and deionized water. The hydrothermal method is a single crystal growth technique. The crystals are then grown from hot aqueous solutions at high temperatures and vapor pressures, for example in Teflon-lined autoclaves. It grows at high temperatures and pressures inside the
[0055] Suitably, the step of associating the modified fabric with lithium metal comprises adding lithium, preferably or molten lithium metal. Preferably, this is done by injecting the modified fabric. This can be accomplished by contacting the end of the electrode with molten lithium metal.
[0056] Preferably, the associating step is carried out under an inert atmosphere, preferably an argon atmosphere. It is held.
[0057] In a preferred embodiment, the method further comprises the steps of: In other words, the step of adjusting the injection time. In a preferred embodiment, the injection time is is about 3 mg cm -1 The lithium mass loading is controlled to provide a
[0058] Suitably, at least one of the lithophilic materials is nanostructured. The morphology increases the surface area of the host. Preferably in the form of nanoflakes, most preferably 3D hierarchical MnO2 nanosheets. Typically, they grow on the surface of the fabric, especially on the fabric fibers. MnO2, SnO2, ZnO, Co3O4 Most preferably, the ultrathin nanosheets of the lithophilic material are metal oxides such as carbon. It is produced uniformly on the fibers. This arrangement significantly increases the surface area of the fabric.
[0059] Preferably, in the energy storage device described herein, the cathode is an ethylene / sulfur cathode, preferably a polysulfide, to reduce the shuttle effect; and / or graphene with an appropriate selectively modified interlayer to reduce the charge transfer resistance In one embodiment, an example of such an intermediate layer is, for example, a sulfur / graphite cathode. Boron nitride / graphene (FBN) nanosheets for providing cathodes / G) intermediate layer.
[0060] Suitably the cathode is a free standing cathode.
[0061] In particularly preferred embodiments, the cathodes described herein are flexible cathodes.
[0062] In particular, the graphene / sulfur cathode protected by the FBN / G interlayer is a sulfur-containing polymer of the present invention. When used in devices with polymer-modified separators, the synergistic effects between these elements are To this end, energy storage devices must have high volumetric and gravimetric energy densities. can reach long cycle life even under folded or bent conditions. .
[0063] In a third aspect of the present invention, a lithium metal anode; a cathode comprising sulfur and one or more conductive materials; a separator as defined in the first aspect of the present invention disposed between the anode and the cathode; An energy storage device is provided comprising:
[0064] a lithium metal anode as defined in the third aspect of the present invention; a cathode comprising sulfur and one or more conductive materials; a separator disposed between the anode and the cathode. is also stated.
[0065] a lithium metal anode as defined in the first aspect of the present invention; a cathode comprising sulfur and one or more of a plurality of electrically conductive materials; a separator as defined in the first aspect of the present invention disposed between the anode and the cathode; Also described is an energy storage device comprising:
[0066] In a preferred energy storage device of the present invention, the one or more anodes and cathodes are self-contained. In other words, no additional current collector components, particularly metal current collectors, are required, and the present invention The anode and / or cathode described in the document are used in an electrochemical cell, and the conductive fabric and and / or the graphene in the cathode is sufficiently conductive to eliminate the need for additional current collecting elements. This advantageously means that the mass of the device can be reduced, making it possible to Higher gravimetric and volumetric energy densities are possible in the devices used. This means that it is possible.
[0067] In a particularly preferred embodiment, the energy storage device of the present invention is a flexible energy storage device. Flexibility means that the device can be easily moved without a significant increase in electrical resistance. bending the respective elements and / or the energy storage device without losing electrical conductivity This means that it can be folded, folded, or subjected to one or more physical deformation forces. For example, The preferred conductive fabric is folded at 90 degrees or end-to-end under the weight of the fabric. When subjected to a manual deformation force such as a crease, e.g. a 180° fold, the resistance is reduced by 50% of its original value. %, more preferably 25% or less, and most preferably 10% or less of the electrical resistance.
[0068] Suitably, one or more of the anode, cathode and separator are flexible and suitably movable. When enclosed in a flexible housing it forms a flexible energy storage device. The components of the energy storage device are housed in a flexible housing, preferably a flexible pouch, e.g. The device is enclosed in a flexible Al-plastic membrane envelope. A particularly preferred enclosure is a moisture-tight enclosure. I don't.
[0069] Preferred energy storage devices are: A conductive fabric modified with one or more lithophilic materials for use in an energy storage device. a flexible lithium metal anode; a flexible cathode comprising sulfur and one or more conductive materials; A flexible separator for an energy storage device, the separator having a L i. A porous membrane of an ion-selectively permeable material, at least some of the pores of the porous membrane are connected to the anode and a separator associated with the porous sulfur-containing polymer disposed between the cathode; , Equipped with.
[0070] Particularly preferred energy storage devices are Energy-Efficient Conductive Fabric Modified with 3D Hierarchical MnO2 Nanosheets Lithophilic Materials - a flexible lithium metal anode for a storage device; A flexible graphene / sulfur cathode protected by an FBN / G interlayer; A flexible separator for an energy storage device, the separator having a L i) a microporous membrane of an ion-selectively permeable polyolefin material, Some involve nanoporous polysulfone polymers disposed between the anode and cathode. The separator attached to the Equipped with.
[0071] A preferred device includes a cathode, an anode, a separator, an electrolyte, and a current collector. All components within a flexible battery, including the battery itself, maintain a continuous electron / ion pathway to prevent battery failure. The present invention provides a method for manufacturing a semiconductor device that is mechanically flexible and capable of withstanding repeated mechanical deformations while preventing mechanical deformations. The flexible energy storage device has ultra-long cycle life and high energy density. All elements exhibit excellent mechanical flexibility and electrochemical performance. properties that enhance the battery's electrochemical properties when repeatedly bent or folded. The volume change of the lithium anode and the growth of dendrites contribute to the fabric’s functionalization. Limited by the stable conductive interconnect network of the sulphur-containing polymers. The improved separator improves the mechanical performance and thermal stability of the separator, improving the safety of the entire battery. Both the cathode and the separator are polysulfide-capturing and poly Modified to block the path of polysulfides to the anode, thus reducing the shuttle effect will be done.
[0072] The free-standing ultra-stable lithium cloth anode of the present invention, the sulfur-containing polymer modified separator of the present invention , and a device containing a free-standing graphene / sulfur cathode protected by an FBN / G interlayer. The device allows for devices with both extremely high energy density and mechanical flexibility. to.
[0073] Suitably, the energy storage device further comprises an electrolyte. A preferred electrolyte is lithium. It is an organic liquid containing ammonium salts.
[0074] Preferably, in the energy storage device of the present invention, the electrolyte has a molecular weight of about 5 / 1 to 30 [ mLg -1 In a preferred embodiment, the electrolyte is present in an electrolyte to sulfur (E / S) ratio of 0.1 to 0.5. The sulfur (E / S) ratio is approximately 20 / 1 [mLg -1 ].
[0075] Suitably, the electrolyte comprises an organic electrolyte in combination with lithium ions, for example one or more lithium salts. In one preferred embodiment, the electrolyte is a liquid such as, for example, Examples include LiTFSI and LiNO3. In one preferred embodiment, The solution was 1 M LiTFSI in DOL / DME containing 1 wt % LiNO3.
[0076] Particularly preferred energy storage devices have a capacity of at least 800 cycles at a current density of 0.5°C. After cooling, it retains up to 60% of its initial capacity.
[0077] Particularly preferred energy storage devices have at least one foldable capacity after 800 cycles. Both are about 100WhL -1 , more preferably at least about 300 WhL -1 , most preferably is at least about 500WhL -1 The volumetric energy density of
[0078] Particularly preferred energy storage devices have a minimum of 10% energy storage capacity after 800 cycles in the folded state. At least about 75WhKg -1 , more preferably at least about 250 WhKg -1 , most preferred Preferably at least about 470WhKg -1 The gravimetric energy density is shown.
[0079] In one embodiment, the folded state refers to a bending angle of 90° or less. , The folded state means a bending angle of 180° or less.
[0080] A particularly preferred energy storage device is one that contains approximately 10 ... Approximately 3,500mAhg -1 Indicates the capacity of.
[0081] A preferred energy storage device comprises one or more of an anode, a cathode, and a separator. is flexible and has a maximum initial capacity of 0.5C after at least 800 cycles at a current density of 0.5C. It can be bent to a 90° configuration while retaining approximately 60%.
[0082] A further preferred energy storage device is a device comprising an anode, a cathode, and a separator. 1 or more is flexible and has an initial capacity after at least 800 cycles at a current density of 0.5C It can be folded in a 180° configuration while retaining up to approximately 60% of its original size.
[0083] The term "about" generally means from ±5% of the stated value unless otherwise specified. do.
[0084] In a fourth aspect of the present invention, a polyimide is used as a pore filler for a porous membrane of a Li-ion selectively permeable material. The use of a porous sulfur-containing polymer is provided. Preferably, the pores are filled with Li-ion selective The electrically permeable material is useful in energy storage devices, particularly lithium sulfur energy storage devices. It is used as a separator for
[0085] In a fifth aspect of the present invention, there is provided a use of a separator for an energy storage device, comprising: The separator includes a porous membrane of one or more Li-ion selectively permeable materials, the porous membrane being This is related to porous sulfur-containing polymers in gas storage devices, particularly lithium-sulfur batteries. do.
[0086] In an energy storage device, particularly a lithium-sulfur battery, one or more lithophilic materials The use of a lithium metal anode comprising a conductive cloth modified with has also been described.
[0087] In a sixth aspect of the present invention, a separator according to the first aspect and a lithium metal anode according to the second aspect are provided. and / or an electronic device comprising the energy storage device of the third aspect. Preferably, the electronic device is a wearable device. Suitably, The electronic device is an electronic clock, and an LED or LED screen. [Brief description of the drawings]
[0088] [Figure 1] A schematic diagram of the design and fabrication of the flexible Li-S full battery is shown in Figure 1. The flexible Li-S full battery was fabricated using a lithium cloth anode, a PSU-Celgard separator, and a free-standing graphene / sulfur cathode protected with an FBN / G interlayer. [Diagram 2] Figure 2 shows the fabrication and characterization of the lithium cloth anode, where (a) is a schematic diagram of the material design and the resulting synthesis procedure, (b-d) are SEM images of the modified carbon cloth, (e-g) are SEM images of the obtained lithium cloth, (h) is an optical photograph of the twisted lithium cloth, and (i) is the XRD patterns of the modified carbon cloth and lithium cloth. [Diagram 3] Figure 3 shows the electrochemical and mechanical stability of the symmetric pouch battery based on the lithium cloth electrode. (a) Galvanostatic cycling performance of the symmetric pouch battery based on the lithium cloth electrode in flat and bent states; (b) schematic diagram of the assembled symmetric pouch battery; (c) voltage profiles for 100, 200, and 250 cycles; (d) full Li-stripping curve of the Li cloth electrode vs. Li+ / Li up to 1 V; (e) SEM image of the lithium cloth electrode after the 250th stripping; and (f, g) SEM images of the lithium cloth electrode after the 250th stripping / plating. [Figure 4]FIG. 4 shows the fabrication and characterization of the PSU modified separator, with (a) a schematic diagram of the synthesis procedure for PSU-Celgard separator, (b) pristine Celgard 2400, (c) top view SEM image of the PSU Celgard separator, (d) side view SEM image of the pristine Celgard 2400, (e) side view SEM image of the PSU-Celgard separator, (f) TGA curves of pristine Celgard 2400 and PSU-Celgard separator, (g) FTIR spectra of pristine Celgard 2400 and PSU-Celgard separator, (g) ionic conductivity of pristine Celgard 2400 and PSU-Celgard separator, (i) contact angle of electrolyte on pristine Celgard 2400 and PSU-Celgard separator, and (j) optical photograph of the H-bottle system with PSU separator. [Diagram 5] Figure 5 shows the electrochemical performance of the Li-S test coin cells: (a) charge / discharge curves of the Li-S test cell at 1, 50, 100, 200, and 500 cycles; (b) cycle performance of the Li-S test cell and the Li-S control cell; (c) rate performance of the Li-S test cell and the Li-S control cell; (d-k) low and high magnification SEM images of various anodes and separators after 500 cycles: (d,e) lithium cloth anode, (f,g) lithium foil anode, (h,i) PSU-Celgard separator, and (j,k) Celgard separator. [Figure 6]Figure 6 shows the electrochemical performance and application of the flexible Li-S pouch battery, where (a) is a schematic diagram of the structure of the flexible Li-S pouch battery, (b) is the charge / discharge curves of the Li-S pouch battery, (c) is the cycle performance of the Li-S pouch battery, (d) is the charge / discharge curves of the soft package Li-S battery bent at different angles, (e) is the comparison of the volumetric (Wh Lcell-1) / weight (Wh kgcell-1) energy density of the reported flexible Li-S battery, (f) is the optical photograph of the flexible Li-S full-cell power LED light in the bent state, (g) is the optical photograph of the electric clock in the bent state, and (h, g) are the optical photographs of the LED screen with a single chip, where (h) is in the flat state and (i) is in the bent state. [Figure 7] Figure 7 shows photographs of (a) carbon cloth and (b) modified carbon cloth in contact with molten lithium, and (c) lithium cloth obtained at lithium mass loadings of ~3 mg cm-2 and (d) ~6 mg cm-2. [Figure 8] FIG. 8 shows the nitrogen adsorption isotherms of the modified carbon and lithium cloths. [Figure 9] FIG. 9 shows low and high magnification SEM images of a commercial carbon cloth. [Figure 10] Figure 10 shows (a) a photograph of the free-standing graphene / sulfur with an FBN / G interlayer, (b) an SEM image, (c) a low-magnification SEM image of the FBN / G interlayer, and (d) a high-magnification SENM image. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0089] The inventors have developed an ultrastable lithium cloth anode, a polysulfone-modified separator, and a self-supporting Flexible and fabricated cathodes using a novel sulfur / graphene / boron nitride nanosheet cathode We have devised a lithium-sulfur all-cell battery with high thermal conductivity. We have succeeded in controlling the shuttle effect and dendrite formation. Therefore, the flexible lithium-sulfur all-cell battery has excellent mechanical flexibility and excellent electrochemical performance. It exhibits an ultra-long cycle life of 800 cycles in the folded state, and an unprecedented 497W hL -1 High volumetric energy density of 463.6Whkg -1 High gravimetric energy density This has been achieved.
[0090] [Table 1]
[0091] Experimentally, 3 mg cm -2 a lithium cloth anode, a cathode having an intermediate layer, and The mass of the PSU-Celgard separator is 9.3 mg cm -2 , 6.5mg c m -2 , and 1.35 mg cm -2 The measured values of the lithium cloth and the cathode are The thickness is standard stress (400Ncm -2 , the pressure used to compress a standard coin cell The thickness of the separator is usually about 25 μm. Weight density and volume The density is calculated based on the total weight and volume of the current collector, electrodes, and separator.
[0092] The flexible Li-S full battery of the present invention is made up of an ultra-stable lithium cloth anode, polysulfone (PSU ) modified separator and free-standing graphene / sulfur protected by FBN / G interlayer Based on a 100% pentacene cathode, it allows for both very high energy density and mechanical flexibility. The ultrastable flexible lithium cloth anode is fabricated by injecting molten lithium into a pre-modified carbon cloth. The modified carbon cloth is produced by coating it with lithium via implantation. The properties and hierarchical nanostructured networks provide unprecedented flexibility and stability for lithium cloth electrodes. In addition, the commercially available separator Celgard 2400 has a vacuum and and a phase inversion process, resulting in smaller pore size and improved thermal and The synergistic effect of the PSU filler and the FBN / G interlayer provides the best possible The final battery reaches a long cycle life of 800 cycles in the folded state, which is very high Volumetric energy density: 497WhL -1 and gravimetric energy density of 464Whkg -1 reached One flexible Li-S pouch battery can power multiple LED lights or electronic The three connected flexible batteries can power the clock in both flat and curved positions. The single chip operates at a nominal voltage of 5V and lights up an LED screen in both standby and standby states. It is possible.
[0093] result Flexible LS full battery design FIG. 1 shows a flexible Li- The structure of the S full battery is shown. The flexible anode, lithium fabric, is a 3D lithophilic M was synthesized by pre-storing lithium on carbon cloth modified with nO2 nanoflakes. A novel approach of the "phase inversion" process was used to fabricate a commercial separator with PSU. The large pore size of the cathode was reduced. To coat the free-standing graphene / sulfur cathode, FBN was used. / Graphene intermediate layer was adopted.
[0094] Lithium Cloth Electrode The fabrication of lithium fabric involves the modification of carbon fabric with 3D lithophilic nanostructures. , two steps of storing Li into the modified host by the molten lithium injection process (Figure 2a). Excellent lithophilicity of the host material is a prerequisite for molten Li injection. Commercially available carbon cloth has low lithophilicity and does not adsorb molten lithium (Fig. S1a). 3D hierarchical MnO2 nanosheets grown on the surface of carbon cloth to improve lithophilicity This provides the carbon cloth with not only excellent lithophilicity but also a large surface area. The second step is to uniformly inject Li into the modified carbon cloth. By simply contacting the edge of the modified carbon cloth with molten Li, fast and uniform Li uptake could be achieved. (Fig. S1b). The silvery lithium spreads quickly throughout the fabric, and a flexible lithium fabric is finally obtained. The amount of lithium pre-stored in the modified carbon cloth can be controlled by adjusting the injection time. The morphology of the modified carbon fabric and the resulting lithium fabric can be controlled (Fig. S1c and d). and the structure is shown in Figure 2.
[0095] Fabrication and performance of lithium cloth anodes. Figure 2a shows a schematic of the material design and the resulting synthesis procedure. d is the SEM image of the modified carbon cloth, Fig. 2e–2g are the SEM images of the obtained lithium cloth, Fig. 2h is an optical photograph of the twisted lithium fabric, and Fig. 2i is an optical photograph of the modified carbon fabric and lithium fabric. Figure 2b shows the XRD pattern of the modified carbon fabric. Figure 2b shows the low magnification top-view SEM image of the modified carbon fabric. The typical fiber structure of the porous interlaced microstructure is clearly visible. The SEM image in Fig. 2c shows a high magnification top view of the modified carbon fabric, and Fig. 2d shows the hierarchical Mn Side-view SEM image of the O2 nanostructure. A 3D hierarchical network constructed from ultrathin nanosheets. It can be clearly seen that the carbon fiber is uniformly coated with the fabric. Figures 2e and 2f show that the surface area of the ZnO-based ... -2 This is a low magnification SEM image of the lithium cloth. The lithium cloth also has an interlaced structure. High-magnification SEM images (Fig. 2g) show that the inner space of the porous network is filled with lithium. The results show that lithium is distributed in the interstices between the fibers and in the nanoscale network. The lithium cloth obtained was completely confined within the workpiece. The XRD pattern of the lithium fabric showed that it easily twisted (Fig. 2h), indicating the excellent flexibility of the lithium fabric. (Figure 2i) shows the presence of lithium accumulated in the fabric.
[0096] The electrochemical sustainability of the flexible lithium fabric was investigated using a symmetric pouch battery. Two identical lithium cloth electrodes were assembled into a pouch battery, as shown in Figure 3b. The aluminum cloth electrode is 3mg / cm 2 The mass loading is about the same as that of lithium. Ring performance is 1mAcm -2 and 3mAh cm -2 The capacitance density of The symmetric lithium-cloth battery showed a stable voltage of about 120 mV for 100 cycles (Fig. 3a). The voltage hysteresis is due to the sum of the Li stripping and Li plating overpotentials. After 100 cycles, the fence is folded and another 100 cycles are continued. The flat voltage plateau in both the charging and discharging states is consistent with the hysteresis. The voltage was maintained throughout the entire 100 cycles without any obvious increase. After 200 cycles, The pond was expanded and cycled an additional 50 times. The results showed that the cells still had excellent size. The device shows stable clocking and consistently low hysteresis. To investigate further, the 1st (flat state), 200th (bent state), and 200th A close-up of the symmetric cell at the 10th cycle (plateau) is shown in Figure 3c. No clear increase in voltage hysteresis was observed between the profiles, and both the bent and flat conditions The lithium cloth electrode has high stability and flexibility. As shown in Figure 3d, the ZnO-based ... When charged to 1V, it produces about 3536mAhg -1 capacity (based on the weight of lithium) This is very close to the theoretical capacity of a pure Li anode (compared to pure Li). Therefore, the modified carbon fabric of the present invention has high cycle stability. Attractive possibility of producing high performance lithium anodes with both quality and capacity The morphology of the lithium cloth electrode after multiple plating / stripping cycles is presented. - To confirm the change, the symmetric pouch battery was stripped 250 times and High magnification SEM image of the lithium cloth electrode. The image (Fig. 3e) shows that the spaces in the network that were originally filled with metallic Li have been emptied as the Li has been removed. This indicates that after the initial Li injection, the structure returned to its previous 3D hierarchical porous structure. It also shows that the surface nanostructure remains unchanged during cycling. Most of the space in the porous structure was filled again (Fig. 3f), and the morphology of the electrode after lithium injection was Low magnification SEM of the lithium cloth electrode after 250 cycles shows that 1 shows a smooth surface of the lithium cloth without dendrite formation.
[0097] Electrochemical and mechanical stability of symmetric pouch batteries based on lithium cloth electrodes Figure 3a shows the constant current (VDC) of a symmetric pouch battery based on a lithium cloth electrode in flat and bent states. Figure 3b shows the current cycling performance of the assembled symmetric pouch battery cell. Figure 3c shows the voltage profiles at the 100th, 200th, and 250th cycles. Figure 3d shows the Li + Complete Li charge of Li cloth electrodes up to 1V vs. Li Stripping curves are shown. SEM of lithium cloth electrode after 250 strippings. The image is shown in Fig. 3e, SEM of the lithium cloth electrode after 250 stripping / plating The images are shown in Figures 3f and 3g.
[0098] Fabrication and characterization of PSU modified separators Figure 4a shows a schematic diagram of the synthesis procedure for the PSU-Celgard separator. The top view SEM image shows the pristine Celgard 2400 and Figure 4c shows the PSU-Celgard Figure 4d shows a top view SEM image of the separator. Figure 4c shows a side-on SEM image of PSU-Celgard. F is the TGA curve of Pristine Celgard 2400 and PSU-Celgard separator. Figure 4g shows the FTIR spectrum, and Figure 4h shows the ionic conductivity. 1 shows an optical photograph of an H-bottle system with a parater.
[0099] The synthesis procedure of PSU-Celgard separator includes the coating step, as shown in Figure 4a. The process consists of three steps: a vacuum step, and a wetting step. Compared to the previous coating strategy, an additional layer of coating material is removed from the surface of the Celgard separator. The large pores remaining in the separator are filled with PSU after the vacuum step, and the coating material The weight of PSU was significantly reduced. Also, a phase inversion strategy was used to create micropores in the PSU. When the polymer and DMF (solvent phase) were immersed in water (non-solvent phase), thermodynamic equilibrium was instantly achieved. The mixture collapsed and two phases were formed: a polymer-rich phase and a polymer-poor phase. Solvent-nonsolvent exchange The process occurred immediately at the slurry / water interface, resulting in a porous structure (inset in Figure 4a). The mass loading of the PSU is 0.12 mg cm -2 The commercially available Celguard separator Large pores (larger than 100 nm) can be observed (Figure 4b). After combining with PSU, the pores The separator frame is still clearly visible (Fig. 4c), and its thickness (approximately 25 μm) is The thickness of the separator is approximately the same as the original thickness of the separator (approximately 26 μm) (Figures 4d and 4e). Compared to most previous strategies in which an additional layer is coated onto a commercially available separator, this method This would facilitate the reduction of the thickness of the final battery. The thermal stability of the separator was evaluated using a thermogravimetric analysis. The results were investigated using a thermogravimetric analyzer (TGA) (Figure 4f). The decrease starts at 250°C, whereas the PSU-Celgard separator decreases up to 360°C. There is no weight change, and a second weight loss occurs at about 500°C. This higher thermal stability is due to the introduction of more stable PSUs with higher melting points around 520°C. The surface chemical changes of the PSU-modified Celgard separator are , and was evaluated by Fourier transform infrared spectroscopy (FTIR) (Figure 4g). In addition to all the characteristic peaks, 1583 cm -1 , 1335cm -1 , and 1153 cm -1 Three new peaks were observed in the spectrum, which correspond to the benzene ring of PSU, sulfur The bands correspond to the stretching vibrations of aryl groups (C-SO2-C) and sulfonyl groups (O=S=O), respectively. This indicates that the introduction of PSU into Celgard separators was successful. The ionic conductivity of the Celgard separator before and after filling with U was measured using a stainless steel symmetric cell. The results were evaluated using the Celgard separator and the PSU-Celgard separator. The temperature dependence of the ionic conductivity of both is shown. The activation energy is given by the following Arenius was estimated using the formula
number
[0100] Electrochemical performance of Li-S coin cells To evaluate the performance of the new anodes and separators, test coin cells were Anode made of aluminum fabric, PSU-Celgard separator and FBN / G interlayer protected glass. The rhenium / S cathode was fabricated using highly porous graphene as the host for the sulfur cathode. The free-standing graphene / sulfur cathode is a mixture of graphene and high surface area graphene. The cathode was further coated with an FBN / G interlayer to protect it. The results are shown in Figure S4.
[0101] Electrochemical performance of Li-S test coin cells Figure 5a shows the Li-S coin cell at 1, 50, 100, 200, and 500 cycles. 5b shows the charge / discharge curves of the 1000-mAh battery, FIG. 5b shows the cycling performance, and FIG. 5c shows the charge / discharge curves of the 1000-mAh battery. The rate performance of the Li-S cell and the control Li-S cell is shown. Low and high magnification SEM images of various anodes and separators are shown in Figures 5d to 5k. The lithium cloth anode is shown in Figure 5d and Figure 5e, and the lithium foil anode is shown in Figure 5f and Figure 5g. 5g, PSU-Celgard separator, 5h and 5i, Celgard separator is shown in Figures 5j and 5k.
[0102] The mass loading of sulfur in the cathode is 2 mg / cm 2 Figure 5a shows the results of the experiment with a 0.2C current. The discharge / charge curves of a Li-S test battery at various cycles at different current densities are shown. The discharge / charge plateaus are well-retained even after 500 cycles. The ring performance is shown in Figure 5b. A Li-S coin cell with a phene / sulfur cathode is used as the control cell. The test battery had a capacity of 1320mAh g at a current density of 0.2C. -1 provides an initial discharge capacity of The amount is 1100mAh g even after 500 cycles -1 Li-S battery cycle The decay rate per unit time was about 0.0334%, which was lower than the decay rate of the control battery (about 0.15%). The rate performance of the test cell is 0.2C, 0.5C, 1C, 2C, and 3C. Rate: 1200mAh g -1 , 1112.8mAh g -1 , 1020.5 mAh g -1 , 921mAh g -1 , and 877mAh g -1 Holds a large capacity of To investigate the morphological changes of the anode and separator, A post-mortem analysis was performed after 500 cycles. After 500 cycles, the surface of the lithium cloth anode was Moreover, no lithium dendrites are found (Fig. 5d and In contrast, the surface of the Li foil electrode in the control battery was randomly distributed after 500 cycles. The typical lithium dendrite morphology arranged in the lattice is shown in Fig. 5f and The formation and growth of lithium dendrites is driven by the continued inflow of electrolyte and fresh lithium. This can result in significant consumption, ultimately causing electrolyte depletion and electrode collapse. This may be the cause of the larger decay in the control cell. SEM image of PSU-Celgard separator after 0 cycles. No large pores are visible. In addition, some of the pores in the commercially available separators were damaged after 500 cycles. It has grown so much.
[0103] Flexible Li-S pouch battery A flexible Li-S pouch full battery was fabricated as shown in Figure 6a. Sulfur composite material is 3.5 mg cm -2 It is used as a cathode with a mass loading of about 10000g (sulfur). After adding a suitable electrolyte, the pouch cell is The tube was sealed in an Al plastic film envelope. Figures 6b and 6c show the flat / Charge Curves and Cycling Properties of Flexible Li-S Pouch Batteries in Constant and Bent States Two discharge / charge plateaus are clearly observed in both the flat and bent states. As can be seen, the discharge capacity of the battery in the flat and bent states is 5.13mAh, respectively. g -1 and 5.02mAh g -1 The cycle performance of the battery was tested in a 180° bent state. The capacity was tested and retained up to 60% of the initial capacity after 800 cycles at a current density of 0.5C. This ultra-long life is due to the excellent properties of the lithium cloth anode and graphene / sulfur cathode. This can be attributed to the mechanical properties and electrochemical stability of the battery. The capacity is tested during the bending process (Fig. 6d and inset). No visible defects were observed, indicating stable electrochemical performance under bending. The product energy density and gravimetric energy density are calculated based on the battery parameters. (Table S1). Previously reported data for flexible Li-S batteries 35-40 Compared to Richter, Current Li-S all-cell batteries based on a graphene cloth anode and graphene / sulfur cathode have 7WhL -1 and 464Whkg -1 Higher volumetric energy density and higher weight percent The energy density is shown in Fig. 6e.
[0104] Electrochemical performance and applications of flexible Li-S pouch batteries FIG. 6a shows a schematic diagram of the structure of a flexible Li-S pouch cell, and FIG. 6b shows the charge / discharge curves. 6c shows the cycling performance of the Li-S pouch battery, and FIG. 6d shows the cycling performance of the Li-S pouch battery at various angles. Figure 6e shows the charge / discharge curves of a soft-packaged Li-S battery bent at 100°C. Reported flexible Li-S battery volumes (Wh L cell -1 ) / Weight(Wh kg cel l -1 ) energy density comparison. Flexible Li-S full battery power source LE in bent state Optical photograph of the D-light (Fig. 6f), an optical photograph of the electric clock in the folded state (Fig. 6g), and LED screen with a single chip in flat (Fig. 6h) and bent (Fig. 6h) states. This is an optical photograph of the
[0105] Flexible Li-S all-cell batteries are ideal power sources for flexible and wearable devices. To demonstrate its functionality, the resulting Li-S pouch battery was applied to power electronic devices. The bent pouch battery contains five red light-emitting diodes (LEDs, The inset in the lower right corner shows the LED in a dark environment. The same LED model is shown when it is lit with a Li-S pouch battery. The clock was powered and functioned normally (Figure 6g). An LED screen with a single chip microprocessor was installed. The nominal operating voltage of the processor is 5V, whereas the discharge plateau of the Li-S battery is 2.3V. and 2.1V, so you can connect three Li-S pouch batteries together to achieve a voltage higher than 5V. When the battery is flat or bent at an angle of more than 90°, the LED screen may It lights up and displays a clear caption that reads "Flexible LiS Deakin University" The resulting flexible Li-S pouch battery exhibited high energy density and excellent mechanical properties. Therefore, the lithium-based fabric has been developed with interesting flexibility and excellent electrochemical performance. Li-S batteries based on 100% hydrogen have great potential for flexible electronic device applications.
[0106] The inventors have developed an ultra-stable lithium cloth anode, a polysulfone (PSU) modified separator, and modified boron nitride / graphene (FBN / G)-protected free-standing graphene / sulfur cathodes. The lithium cloth anode is a flexible Li-S pouch battery that contains a molten lithium-injected plate. The process allows lithium to be stored in the micro / nanoporous structure of the modified carbon fabric. The new flexible pouch battery has several advantages: (1) Lithium Both the fabric anode and the graphene / sulfur cathode are free-standing and do not require additional metal current collectors. All elements retain excellent mechanical flexibility and can withstand repeated bending and folding. (2) The volume change of the lithium anode ensures excellent electrochemical performance of the battery when it is charged. The dendritic growth and formation of a stable conductive interconnected network of modified carbon fibers (3) By adding PSU to the polyethylene separator, The improved mechanical performance and thermal stability of the polyethylene separator further improves the safety of the entire battery. (4) The synergistic effect of the PSU-coated separator and the FBN / G interlayer improves the These lead to the superior performance of the flexible full-cell Li-S battery. The life of the flexible pouch battery can reach 800 cycles in the folded state, and the volume energy -Density and gravimetric energy density are 497WhL -1 and 464Whkg -1 Yes One flexible Li-S pouch battery can power an LED light or an electronic clock. The three connected batteries can be shunted to a nominal voltage of 5V in both flat and bent positions. The research is aimed at developing a high-energy-density LED screen with a single chip. Highlight the promising practical applications of Li-S batteries in flexible energy storage devices.
[0107] material and method Synthesis of Lithium Cloth: The lithium cloth was prepared in two steps. First, a commercially available carbon cloth was heated. The nanosheets were modified with a 3D network of MnO2 nanosheets using the aqueous method and a 1.25 mmol per Potassium manganate (KMnO4) powder and 5 mmol of concentrated hydrochloric acid in 34 mL of deionized water. The precursor solution was prepared by adding 100 mL of the precursor solution to a 45 mL Teflon-lined alumina tube. The mixture was transferred to a toclave and a carbon cloth was placed in the solution. The toclave was heated in an oven at 140°C for 30 minutes. After heating, the samples were washed and The as-modified carbon cloth was then placed in an argon-filled glove box. The modified carbon cloth was placed on the surface of molten Li. The lithophilic nature of MnO2 allowed the cloth to be attached to the molten Li. It can be easily wetted and filled to form a stable lithium cloth.
[0108] Fabrication of symmetrical lithium cloth pouch batteries: Comparison with commercially available soft Al plastic film encapsulated batteries. The lithium cloth pouch battery is packed with two pieces of lithium cloth and a separator (Celgard 2400) The electrodes were assembled in an argon-filled glove box using 1 wt.% electrolyte. It was 1MLiTFSI in DOL / DME with LiNO3.
[0109] Synthesis of PSU-Celgard separator: First, 2.5 g of PSU pellets were mixed with 7.5 g of The solution was then stirred and heated at 80°C for 10 hours. The resulting solution was applied to a commercially available Celgard 2400 separator equipped with a doctor blade. The separator with the PSU coating was placed in a vacuum and adjusted to a thickness of 200 μm. After evacuation, the PSU on the surface of the separator was wiped off. After washing with water, it was dried in an oven at 60°C.
[0110] Synthesis of free-standing graphene / sulfur cathode with FBN / G interlayer: Graphene / sulfur electrodeposition To synthesize the pole, 12 wt. % highly porous graphene (Graphene Supermarket , USA), 8 wt% high surface graphene (Graphene Supermarket, USA), and A mixture of 80% by weight of sulphur and 80% by weight of sulphur was heated at 300°C for 24 hours in a closed vessel. The graphene / sulfur cathode was fabricated by suction filtration. / Sulfur powder is introduced into ethanol saturated with sulfur, the concentration is 8 g L -1 Filter Anodized aluminum oxide membrane (AAO, Wahatman, diameter 47 mm, pore size 0 We used vacuum filtration using a 0.2 μm particle size filter to produce a free-standing graphene / sulfur cathode. The as-obtained free-standing cathode was dried in a vacuum oven at 60 °C for 80 h. These electrodes were further coated with an FBN / G interlayer. The FBN / G interlayer was composed of 20 wt. FBN, 70 wt% graphene, and 10 wt% polyvinyl fluoride binder in N-methylpyrrolidinone (Sigma-Aldrich) solution. The slurry was coated on the surface of the graphene / sulfur cathode and heated in an air oven. It was dried at 60° for 24 hours.
[0111] Fabrication of Li-S coin battery: Lithium cloth anode, PSU-Celgard separator, and A graphene / S cathode with an FBN / G interlayer was used to fabricate Li-S coin batteries. The electrolyte is 1 M LiTFSI in DOL / DME containing 1 wt.% LiNO3. The control Li-S coin cell was charged with lithium foil. A graphene / sulfur cathode was fabricated using a Celgard 2400 anode, a Celgard 2400 separator, and a graphene / sulfur cathode. It is done.
[0112] Fabrication of flexible Li-S pouch batteries: Encapsulating a commercial soft Al-plastic film A fully flexible Li-S battery cell was fabricated using a free-standing graphene / sulfur cathode and a lithium fabric anode. The node was assembled in an argon-filled glove box using electrolyte and sulfur (E / S) ratio is 20 / 1 [mL g -1 ].
[0113] Characterization: using a field emission scanning electron microscope (FESEM, Hitachi s-8600 microscope) The morphology of the samples was investigated using a D8 Advance X-ray diffractometer (Bruk X-ray diffraction (XRD) analysis was performed using a 300 nm fluoride (HF) fluoride-based ... To avoid direct contact, the samples were covered with Kapton tape on the holder. TGA) was performed on a NETZSCH TG 209F1 Libra (NETZSCH) instrument. The Brunauer-Emmett-Teller (BET) surface area of nitrogen is Adsorption was analyzed using a Tristar II 3020.
[0114] Electrochemical measurements: All coin cells and soft packaged cells have less than 1 ppm O The system was assembled in a glove box filled with Ar, Li, and H2O. AC impedance of i-cell (0.1 to 10 with 10 mV amplitude) 6 Hz frequency range), The frequency response was measured using a Solartron 1255B frequency response analyzer. The cling tests were performed with a LAND 8-channel battery tester.
[0115] Embodiment Embodiment 1. A separator for an energy storage device, the separator comprising: and at least one porous membrane of a material selectively permeable to lithium ions, wherein at least one of the pores of the porous membrane is The portion is associated with a porous sulfur-containing polymer, the pores of the sulfur-containing polymer being The pores of the lithium ion selectively permeable material are at least 0.5 orders of magnitude (2 times or more) larger than the pores of the lithium ion selectively permeable material. coefficient), the separator. Embodiment 2. The pores of the porous membrane have an average pore size greater than 100 nm, and the sulfur The average pore size of the yellow-containing polymer is about 50 nm or less, more preferably about 10 nm or less. The separator according to embodiment 1 or embodiment 2. Embodiment 3. The separator comprises one or more microporous membranes of a material selectively permeable to lithium ions. At least a portion of the micropores of the microporous membrane are associated with a nanoporous sulfur-containing polymer. The separator according to embodiment 1 or embodiment 2, Embodiment 4. The sulfur-containing polymer comprises about 10% by weight or less, more preferably about 15% by weight or less. The present invention relates to a cellulose acetate composition comprising a cellulose acetate ester and a cellulose acetate copolymer, and most preferably, the cellulose acetate ester and the cellulose acetate copolymer are present in an amount of about 10% by weight or less. Paraeter. Embodiment 5. The sulfur-containing polymer has a melting point of 250° or more, more preferably 275° or more, and most preferably 280° or more. The separator according to any one of embodiments 1 to 4, preferably having a melting point of 280° C. or more. Ta. Embodiment 6. The sulfur-containing polymer is selectively permeable to lithium ions and electrolytes. and has no selective permeability to polysulfides, as described in any one of embodiments 1 to 5. Separator. Embodiment 7. The pores of the separator are filled with the sulfur-containing zeolite by a method involving a phase inversion step. 7. The separator of any one of embodiments 1 to 6, which is filled with a polymer. Embodiment 8. The sulfur-containing polymer has a concentration of about 0.10 mg cm -2 ~0.2 mg cm -2 8. The separator of any one of embodiments 1-7, wherein the separator is present at a mass loading of Embodiment 9. The sulfur-containing polymer is a sulfonylated polymer, preferably modified or unmodified. Modified aromatic polysulfones, preferably polyarylethersulfones (PAES), e.g. The separator according to any one of embodiments 1 to 8, wherein the separator is, for example, polysulfone. Embodiment 10. The material of the porous membrane is an organic polymer, in particular a polyolefin polymer. The separator according to any one of the first to ninth embodiments, which may be modified or unmodified. Rater. Embodiment 11. The separator according to any one of embodiments 1 to 10, wherein the separator is flexible. The separator described herein. Embodiment 12. The separator has a viscosity of 6.87 mScm at 25°C. -1 Greater ionic conduction 12. The separator according to any one of embodiments 1 to 11, having a thickness of 100 nm to 150 nm. Embodiment 13. A method of preparing a separator for an energy storage device, comprising: (i) providing at least one microporous membrane of a material selectively permeable to lithium ions; providing a porous separator for the energy storage device; (ii) removing the micropores of the porous membrane of at least one lithium ion selectively permeable material; The sulfur-containing polymer modified membrane can be prepared by filling it with at least one sulfur-containing polymer. forming a (iii) introducing nanopores into the sulfur-containing polymer; The method includes:
[0031] Embodiment 14. The step of forming the sulfur-containing polymer modified membrane can be carried out, for example, by solution casting. The solution of the ion-containing polymer in a solvent is dissolved in at least one lithium ion-selective solution by a method according to the present invention. applying a selectively permeable material to a surface membrane of the sulfur-containing polymer; and removing the solution to remove the sulfur-containing polymer. and wiping or brushing off excess polymer from the surface of the surface film. removing excess sulfur-containing polymer from the separator that is not in the pores as a 14. The method of embodiment 13, comprising: Embodiment 15. The step of introducing nanopores into the sulfur-containing polymer comprises: The porous structure is then subjected to a wet phase inversion process to convert the solvent / non-solvent at the phase interface. forming the nanopore structure in the sulfur-containing polymer within the pores of the membrane; The method of embodiment 13 or 14. Embodiment 16. Energy storage device comprising a flexible conductive fabric having an interconnected network of fibers A lithium metal anode for a storage device, wherein each fiber is made of one or more lithophilic materials. The modified fibers are then modified with a material, and lithium metal is injected through the voids or spaces between the modified fibers. A lithium metal anode that is storable and removable. Embodiment 17. The lithophilic material is a hierarchical nanostructure, in particular a nanosheet or nanoframe. 17. The lithiophilic material of claim 16, which forms a network of lithophilic material having a crystalline morphology. Tinium metal anode. Embodiment 18 The lithophilic material is MnO2, SnO2, ZnO, Co3O4, preferably The lithium ion exchanger according to embodiment 16 or embodiment 17, comprising hierarchical MnO2 nanosheets. Metal anode. Embodiment 19. The fabric of the lithium metal anode is interconnected, preferably intertwined. Porous 3D microstructure provided by a network of separated or interwoven fibers and nanostructures on the fibers of the fabric infused with the lithophilic material. 18. The lithium metal anode of embodiment 16 or embodiment 17. Embodiment 20. The fabric of embodiment 16, wherein the fabric has an electrical resistivity of 1.4×10 Ω cm. 19. A lithium metal anode according to any one of claims 1 to 19. Embodiment 21. The lithium ion exchange membrane according to any one of embodiments 16 to 20, wherein the fabric is a carbon fabric. Metal anode. Embodiment 22. The lithium metal is present in an amount of 2 mg cm -2 ~10mg cm -2 Present at a load of The lithium metal anode according to any one of embodiments 16 to 21. Embodiment 23. A method of preparing a lithium metal anode for an electrochemical cell, comprising the steps of: (i) modifying a flexible conductive fabric with one or more lithophilic materials; (ii) associating the modified fabric with lithium metal; The method includes: Embodiment 24. The step of modifying the fabric with the lithophilic material may be, for example, by permanganate. 24. The process according to embodiment 23, which involves a hydrothermal method using potassium gallate powder, concentrated hydrochloric acid, and deionized water. method. Embodiment 25. The step of associating the modified fabric with lithium metal comprises: 23. or 24., which involves the step of injecting lithium, preferably molten lithium metal. 25. The method of embodiment 24. Embodiment 26. A method for controlling the amount of lithium associated with the two by adjusting the injection time. 26. The method of any one of embodiments 23 to 25, further comprising the step of: Embodiment 27. A lithium metal anode and a cathode comprising sulfur and one or more conductive materials. and a cathode between the anode and the cathode, and a separator as described above. Embodiment 28. A lithium metal anode according to any one of embodiments 16 to 22 and a sulfur and a cathode comprising one or more conductive materials; and a conductive layer disposed between the anode and the cathode. and a separator for storing the energy. Embodiment 29. A lithium metal anode according to any one of embodiments 16 to 22 and a sulfur and a cathode comprising one or more conductive materials; and a conductive layer disposed between the anode and the cathode. An energy storage device comprising the separator according to any one of embodiments 1 to 12. Vice. Embodiment 30. The cathode is protected by at least one FBN / G interlayer. The energy storage device according to any one of embodiments 27 to 29. Embodiment 31. A flexible energy storage device, comprising: an anode, a cathode, and and the separator is flexible. Storage device. Embodiment 32. The one or more anodes and the cathode are free-standing. 32. An energy storage device according to any one of claims 1 to 31. Embodiment 33. The anode, the cathode and the separator are contained in a steam-resistant housing. The energy storage device according to any one of embodiments 27 to 32, Embodiment 34. The energy storage device according to any one of embodiments 27 to 33, further comprising an electrolyte. Ghee storage device. Embodiment 35. Folding under the weight of the fabric itself, 90°, or, for example, 180° Even when subjected to manual deformation forces such as end-to-end folding, the resistance remains at 50% or less of its original value. The energy storage device according to any one of embodiments 27 to 34, which maintains an electrical resistance below Chair.
[0036] Embodiment 36. The energy storage device has a current density of at least 80 36. Any one of embodiments 27 to 35, wherein after 0 cycles, the capacity is retained up to 60% of the initial capacity. 2. The energy storage device as described herein. After 800 cycles in a bent state with a bending angle of 180° or less, at least about 100WhL -1, more preferably at least about 300 WhL -1 , and most preferably less At most about 500WhL -1 Any one of embodiments 27 to 35, which shows a volumetric energy density of 1. The energy storage device according to claim 1. 38. After 800 cycles in a folded state, which means a bending angle of 180° or less At least about 75Whkg -1 , more preferably at least about 250 Whkg -1 , Most preferably at least about 470 Whkg -1 An embodiment showing a gravimetric energy density of 27 to 35. An energy storage device according to any one of claims 27 to 35. Embodiment 39. Lithium ion selective permeability of sulfur-containing polymers, preferably polysulfones Use of permeable materials as pore fillers in porous membranes. Embodiment 40. Flexible Lithium-Sulfur Battery in Energy Storage Device Use of a flexible separator, said separator being made of a material selectively permeable to lithium ions. The porous membrane has at least some of the pores associated with a porous sulfur polymer. Used and in use. A flexible lithium battery comprising a conductive cloth modified with a lithophilic material according to embodiment 41.1 or more The use of the metal anode in energy storage devices, in particular flexible lithium-sulfur batteries. Embodiment 42: The separator according to any one of embodiments 1 to 12, and embodiments 16 to 26 The lithium metal anode according to any one of the preceding claims, and / or any one of the preceding claims An electronic device comprising the energy storage device according to any one of claims 1 to 5. Embodiment 43. Electronic watches and wearable devices such as LEDs or LED screens 43. The electronic device of embodiment 42, in the form of a Embodiment 44. A flexible energy storage device comprising 3D hierarchical MnO2 nanosheets. Flexible lithium-ion batteries for energy storage devices containing conductive fabrics modified with lithophilic materials a flexible graphene / sulfur cathode protected by an FBN / G interlayer; and a flexible separator for an energy storage device, the separator comprising a lithium-ion battery. The microporous membrane comprises one or more microporous membranes of selectively permeable polyolefin material, the microporous membranes having a small number of pores. At least a portion of the nanoporous polysulfone is disposed between the anode and the cathode. Flexible energy storage devices associated with polymers.
Claims
1. A separator for an energy storage device, the separator comprising: The device comprises one or more porous membranes of selectively permeable sulfuric acid material, at least some of the pores of each porous membrane being porous sulfuric acid. The pores of the sulfur-containing polymer are associated with the lithium ion-selective A separator having a pore size at least 0.5 orders of magnitude (a factor of 2 or more) smaller than the pores of the selectively permeable material. 。
2. The pores of each porous membrane of the lithium ion selectively permeable material have an average diameter of greater than 100 nm. and the average pore size of the sulfur-containing polymer is about 50 nm or less, more preferably 2. The separator of claim 1, wherein the particle size is about 10 nm or less.
3. The separator comprises one or more microporous membranes of a material selectively permeable to lithium ions, At least a portion of the micropores of the microporous membrane of the sulfur-ion selectively permeable material are nanoporous sulfur-containing. The separator of claim 1 or 2 associated with a polymer.
4. The sulfur-containing polymer comprises no more than about 20% by weight of the separator, more preferably no more than about 15% by weight of the separator.
5. The method of claim 1, wherein the hydroxypropyl ether is present in an amount of about 10% by weight or less, most preferably about 10% by weight or less. The separator according to claim 1.
5. The sulfur-containing polymer is heated to a temperature of 250° C. or higher, more preferably 275° C. or higher, and most preferably The separator according to any one of claims 1 to 4, wherein the melting point is 280°C or higher. 。
6. the sulfur-containing polymer is selectively permeable to lithium ions and an electrolyte; The method according to any one of claims 1 to 5, which does not have selective permeability to polysulfides. Separator.
7. The pores of the separator are filled with the sulfur-containing polymer by a process involving a phase inversion step. The separator according to any one of claims 1 to 6, which is filled.
8. The sulfur-containing polymer has a concentration of about 0.10 mg / cm -2 ~Approx. 0.2mg / cm -2 Mass of The separator according to any one of claims 1 to 7, which is under load.
9. The sulfur-containing polymer is a sulfonylated polymer, preferably a modified or unmodified aromatic Polysulfone, preferably polyarylethersulfone (PAES), e.g. The separator according to any one of claims 1 to 8,
10. The material of the porous membrane comprises an organic polymer, in particular a polyolefin polymer, which The separator according to any one of claims 1 to 9, which may be modified or unmodified.
11. The separator according to any one of claims 1 to 10, wherein the separator is flexible. Data.
12. The separator has a dielectric constant of 6.87 mS cm at 25° C. -1 Has greater ionic conductivity The separator according to any one of claims 1 to 11.
13. 1. A method of preparing a separator for an energy storage device, comprising: (i) providing one or more microporous membranes of at least one lithium-ion selectively permeable material; providing a porous separator for the energy storage device; (ii) removing the micropores of the porous membrane of at least one lithium ion selectively permeable material; The sulfur-containing polymer modified membrane is filled with at least one sulfur-containing polymer. forming a (iii) introducing nanopores into the sulfur-containing polymer; The method includes:
14. The step of forming the sulfur-containing polymer modified membrane may be carried out by, for example, a solution casting method. The solution of the ion-containing polymer in a solvent is dissolved in at least one lithium ion selectively permeable material. and removing said solution to form said sulfur-containing polymer. and wiping or brushing excess polymer off the surface of the surface film to expose the holes. and removing excess sulfur-containing polymer from said separator that is not within said separator. The method according to claim 13.
15. The step of introducing nanopores into the sulfur-containing polymer comprises wet transferring the modified membrane. A phase process is performed to convert the pores of the porous membrane into a solvent / non-solvent mixture at the phase interface. The nanopore structure is formed in the sulfur-containing polymer according to claim 13 or 14. How to.
16. A lithium metal anode, a cathode comprising sulfur and one or more conductive materials, and and a separator located between the cathode and the separator, the separator being a lithium ion battery. and one or more porous membranes of a lithium ion selectively permeable material, each membrane of the lithium ion selectively permeable material being At least a portion of the pores are associated with a sulfur-containing polymer, The pores of the lithium ion selectively permeable material are at least 0.5 orders of magnitude (2 A factor of more than 100x smaller, energy storage device.
17. The separator is a separator as defined in any one of claims 1 to 13.
17. The energy storage device of claim 16.
18. 11. The method of claim 1, wherein the cathode is protected by at least one FBN / G interlayer.
18. The energy storage device according to claim 6 or 17.
19. A flexible energy storage device, comprising: an anode, a cathode and a separator. The energy storage device according to any one of claims 16 to 18, wherein the motor is flexible. 。
20. 20. Any of claims 16 to 19, wherein the one or more anodes and the cathode are free-standing.
3. The energy storage device according to claim 1 .
21. The anode, the cathode and the separator are enclosed in a steam-resistant housing. The energy storage device according to any one of claims 16 to 20.
22. The energy storage device according to any one of claims 16 to 21, further comprising an electrolyte. Chair.
23. The fabric is folded at 90° under its own weight, or the edge is folded at 180°, for example. Even if subjected to manual deformation force such as bending from one end to the other, the electrical resistance remains at 50% or less of the original resistance value. The energy storage device according to any one of claims 16 to 22, wherein the energy storage device holds
24. The energy storage device is capable of withstanding at least 800 cycles at a current density of 0.5C. The energy storage device according to any one of claims 16 to 23, which retains up to 60% of its initial capacity after Ghee storage device.
25. At least about 100 WhL after 800 cycles in a bent state with a bending angle of 180° or less -1 , more preferably at least about 300 WhL -1 , and most preferably at least about 50 0WhL -1 The energy density of the energy storage medium according to any one of claims 16 to 24 is Energy storage device.
26. At least about 75 Whkg after 800 cycles in a bent state with a bending angle of 180° or less -1 , more preferably at least about 250 Whkg -1 , and most preferably at least about 4 70Whkg -1 According to any one of claims 16 to 25, which exhibits a gravimetric energy density of Energy storage devices.
27. The lithium metal anode comprises a flexible conductive fabric having an interconnected network of fibers. each fiber being modified with one or more lithophilic materials, and lithium metal is distributed between the modified fibers. Any one of claims 16 to 26, which is capable of being injected, stored and removed from a void or space of The energy storage device according to claim 1 .
28. The lithium metal anode is a hierarchical nanostructured network of lithophilic materials. The lithophilic material preferably has a nanosheet or nanoflake shape.
28. An energy storage device according to any one of claims 16 to 27.
29. The lithophilic material is MnO 2 , SnO 2 , ZnO, Co 3 O 4 , preferably hierarchical Mn O 2 30. The energy storage device of claim 28 comprising nanosheets.
30. The lithium metal anode has a fabric, and the fabric of the lithium metal anode is interconnected. Porosity provided by a network of interlocking, preferably interwoven or woven fibers. The fabric has a 3D microstructure and a nanostructure on the fibers of the fabric to which the lithophilic material is added. The energy storage device according to any one of claims 16 to 27.
31. The fabric is 1.4 x 10 -3 Any one of claims 16 to 30 having a resistivity of Ω cm. Item 10. The energy storage device according to item 10.
32. The energy storage device according to any one of claims 16 to 31, wherein the fabric is a carbon fabric. Chair.
33. The lithium metal is 2 mg cm -2 ~10 mg cm -2 1. The method of claim 1, 33. An energy storage device according to any one of claims 6 to 32.
34. 1. A flexible energy storage device, comprising: 3D hierarchical MnO 2 Conductive fabric modified with nanosheet lithophilic material A flexible lithium metal anode for an energy storage device. a flexible graphene / sulfur cathode protected by an FBN / G interlayer; A flexible separator for an energy storage device, the separator comprising: The present invention relates to a method for producing a microporous membrane comprising the steps of: The portion is a nanoporous polysulfone polymer located between the anode and the cathode. Associated, flexible energy storage device.
35. A porous sulfur polymer, preferably polysulfone, material selectively permeable to lithium ions Use as a pore filler in porous membranes.
36. Flexible separator in energy storage device, preferably flexible lithium-sulfur battery The use of a separator comprising one or more porous membranes of a material selectively permeable to lithium ions, wherein at least a portion of the pores of the porous membrane are associated with a porous sulfur polymer; use.
37. The separator according to any one of claims 1 to 12 and / or claims 16 to 18.
35. An electronic device comprising an energy storage device according to any one of claims 34.
38. Wearable devices such as electronic watches and LEDs or LED screens.
38. The electronic device of claim 37.
Citation Information
Patent Citations
Lithium sulfur battery anode, preparation method and application thereof
CN105932265A
Lithium sulfur battery anode material and preparation method thereof
CN107863520A
Method for preparing lithium-sulfur battery anode based on catalysis of active MnO2
CN107887605A